Pemetaan dan Pengembangan Klaster Industri Mebel Menggunakan Analisis SWOT (Studi kasus:Kelurahan Gilingan Kecamatan Banjarsari, Surakarta) - Bakdiyono, Eko, Much. Djunaidi, ST, MT, Dr. Suranto, MM (2016)
The furniture industry is an industry where its resources come from nature itself, namely wood and rattan combined with elements of indigenous culture of Indonesia. The mill has a central market kelurahan largest furniture diaerah around Surakarta then had a great chance to develop. The purpose of this study was to determine the strategy of businesses involved in the cluster with the furniture industry sector and the development of the furniture industry in the mill village. This study uses the SWOT method is how to determine the company's strategy to set a strategy or business plan in the short term and long term. IFAS (Internal Strategic Factor Analysis Summary): factors internal strategy of a company that shows the strengths and weaknesses of the company. EFAS (External Strategic Factor Analysis Summary): factors external strategy firm that provides opportunities and threats. In the proposed strategy there are four proposed strategies, namely Strategy SO is to use force to take advantage of opportunities if the company is in cell 1, Strategy WO is to minimize the weaknesses to take advantage of opportunities if the company is in cell 3, T strategies is to use force to overcome the threat if the company is in 2 cells, WT strategy is to minimize weaknesses and avoid threats if the company is in cell 4. The results of the research with the SWOT method with a value of 2.95 and a value IFAS is EFAS 3:22. On the SWOT diagram Cartesian line position is in cell 3 Turn-around is to support the strategy used is the strategy of WO.